Aplikasi Buah Naga Merah Terhadap Penyembuhan Luka Mukosa Rongga Mulut Tikus Wistar - Sari Kusumadewi; Komang Dina Sintya Dewi; IGAA Anggita Dewi Hartayani; Viata Da Silva Pinto (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
Red dragon fruit contains flavonoids that play role in wound healing. The purpose of this study was to determine the effect of red dragon fruit on the healing of oral mucosal wounds of Wistar rats. The research method used post test only control group design by making 3 groups: treatment, positive and negative control. Each group was further divided into 3 small groups based on time: 3, 5 and 7 days, so there were total of 9 small groups with 4 rats each. The research data were analyzed for normality test with Saphiro-Wilk, homogeneity with Levene's test, followed by two-way ANOVA test and LSD Post Hoc. The results were divided into 3 observation groups. Group-1 Epithelial cell thickness: The highest mean value of epithelial cell thickness was in the treatment group on days 3 and 5. Group-2 Number of fibroblast cells: The highest mean value of fibroblast cell: treatment group (63.22) > control group (56.22) > negative group (47.44). Group-3 Angiogenesis: The highest mean angiogenesis value was in the treatment group on days 3 and 5. It was concluded that the application of red dragon fruit (Hylocereus polyrhizus) affected the healing of wistar rats (Rattus norvegicus) buccal mucosal wounds.